2008 IEEE Workshop on Policies for Distributed Systems and Networks 2008
DOI: 10.1109/policy.2008.39
|View full text |Cite
|
Sign up to set email alerts
|

Or Best Offer: A Privacy Policy Negotiation Protocol

Abstract: Privacy policy languages, such as P3P, allow websites to publish their privacy practices and policies in machine readable form. Currently, software agents designed to protect users' privacy follow a "take it or leave it" approach that is inflexible and gives the server ultimate control. Privacy policy negotiation is one approach to leveling the playing field by allowing a client to negotiate with a server to determine how that server collects and uses the client's data. We present a privacy policy negotiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The OBO approach was developed by Walker et al [6] to automate privacy policy negotiation. Their work is intended to establish a privacy policy acceptable to both the client (user) and the data collecting service.…”
Section: Or Best Offer (Obo)mentioning
confidence: 99%
See 1 more Smart Citation
“…The OBO approach was developed by Walker et al [6] to automate privacy policy negotiation. Their work is intended to establish a privacy policy acceptable to both the client (user) and the data collecting service.…”
Section: Or Best Offer (Obo)mentioning
confidence: 99%
“…XACML, while not specifically intended for privacy policy, is sufficiently general that it can also be put to this purpose. However, merging policies leaves no room for negotiation [6]. The need for negotiation is supported by Spiekermann et al [10] who found that user's privacy requirements are not fixed, and can be downgraded in different situations or to achieve a desired outcome.…”
Section: H Summarymentioning
confidence: 99%
“…These tools provide formal approaches for describing privacy policies. With novel functionalities, several privacy policy comparison and negotiation protocols are introduced [11], [2], [1], [14], [9], [8], [13]. However, these methods do not address the privacy management for service aggregation.…”
Section: Introductionmentioning
confidence: 99%